SISTEM PENGAMBILAN KEPUTUSAN DALAM PEMILIHAN JURUSAN MENGGUNAKAN METODE EKSPONENSIAL (MPE) DI PERGURUAN TINGGI NEGERI DAN SWASTA DI JAWA BARAT: Andri Sahata Sitanggang - Jurnal, Redaksi Tim (PETIR, 2018)
Information technology give a lot of convenience that can be perceived by the human life. One example is the information technology era with the birth of the computer in the lives masyarakat..Komputer now felt mamfaat give an awful lot that can not be separated from human life. Every company and institution, in its data processing has been applied by using a computer. Thus the computer can be used as decision support aspects of good and right in taking a decision. Particularly relevant agencies that college is the most important thing when they apply the learning and teaching among faculty and students. It's very important to consider if college graduates want to produce a good and accomplished, then the universities should take steps leading if it is to achieve it. Things can be addressed is the new admissions system kesetiap public and private universities in Indonesia. Why is that, with the existence of a computerized system that will provide convenience in determining the choice of majors to choose, As one of the most important factors is how prospective students can make choices in accordance with their interests and talents. So in their teaching and learning activities will be optimal, there will be complaints that caused the student to have a mind to discontinue their studies. It should be time for a change college party existing systems by creating an information system for the selection of future student majoring in accordance with the desired direction. From this then as a researcher wants to provide input by presenting a new innovation is to build information systems majors elections for state and private universities in Indonesia